Psychopathic Behavior Portrayed in Accident Man (2018) Movie: A Psychoanalytic Approach - Ellyas, Naufal Abyan; Amalia, Syahara Dina (Universitas Muhammadiyah Surakarta, 2023)
This study aims to find the psychopathic behavior portrayed in the movie Accident Man (2018) based on Hare's (2012) twenty types of psychopathic trait also known as PCL-R and the effect of the behavior on the main character life using psychoanalytic approach. This study used qualitative research employing document analysis method. The results of this study reveals seven psychopathic traits done by the main character of the movie, which are superficial charm, lack of remorse, lack of realistic long-term goals, impulsivity, lack of empathy, poor behavioral controls, and criminal versatility. The effect of the psychopathic behavior to the main character life is devastating. It made him to be despised by everyone and made him lose his job even though based on Hare's (2012) PCL-R, the main character cannot be classified as a psychopath because they did not meet the requirements to be categorized as a psychopath. Although he cannot be considered as a psychopath, the seven traits that are revealed in this study suggest that his behavior is always closely related to violence. This study can be used by other researchers who want to study psychopathic behavior further in various literary works and any emerging movie or novel writer that seeks to create a psychopath character by using this study as a reference.